STAGES AND GEOGRAPHICAL ROUTES OF THE DISSEMINATION OF THE WORKS OF MUSLIM EASTERN THINKERS IN EUROPE (Scientific journal of the Fergana State University, 2026)
The article presents the next results of a specialized scientific study devoted to an issue that has so far received little attention in the history of science – the identification of the stages and geographical routes through which the works of Muslim Eastern scholars spread across medieval Europe. Analysis of Arabic and Latin-language sources suggests that between the 10th and 13th centuries, the works of Central Asian scholars entered Europe primarily via two major geographical routes. These include a southwestern route with al-Andalus as the transit hub, and a southeastern route centered around Sicily. The author focuses mainly on the first route, al-Andalus, and concludes that the circulation of Arabic-language works across inland Europe followed three stages: the 10th century, the second half of the 11th century, and the 12th–13th centuries. The article examines the second and third stages of the southwestern, that is, the al-Andalus route of the dissemination of the works of Muslim Eastern scholars.